2011
DOI: 10.1029/2010wr009824
|View full text |Cite
|
Sign up to set email alerts
|

The value of glacier mass balance, satellite snow cover images, and hourly discharge for improving the performance of a physically based distributed hydrological model

Abstract: [1] Physically based hydrological models describe natural processes more accurately than conceptual models but require extensive data sets to produce accurate results. To identify the value of different data sets for improving the performance of the distributed hydrological model TOPKAPI we combine a multivariable validation technique with Monte Carlo simulations. The study is carried out in the snow and ice-dominated Rhonegletscher basin, as these types of mountainous basins are generally the most critical wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(195 citation statements)
references
References 60 publications
7
188
0
Order By: Relevance
“…But they agree with other researchers that incorporating additional site-specific information in a distributed hydrological model increases its robustness (Stisen et al, 2011). Especially remote sensing data are valued as a useful complement to station based time series (Finger et al, 2011;Liu et al, 2012).…”
Section: Improving Spatial Representativeness Of Distributed Modelssupporting
confidence: 50%
“…But they agree with other researchers that incorporating additional site-specific information in a distributed hydrological model increases its robustness (Stisen et al, 2011). Especially remote sensing data are valued as a useful complement to station based time series (Finger et al, 2011;Liu et al, 2012).…”
Section: Improving Spatial Representativeness Of Distributed Modelssupporting
confidence: 50%
“…Contemporary relationships between benthic biodiversity and glacial influence (see, Knispel and Castella, 2003; were then used to inform our future predictions. A range of, hydrological and cryospheric variables were derived from a dynamic catchment hydrological model (TOPKAPI; Ciarapica and Todini, 2002), which has been significantly modified for use in mountainous environments (Finger et al, 2011). TOPKAPI was fed with downscaled climate scenarios (RCM:REMO) for the 2050 horizon (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This makes it rather difficult to find a single parameterization that adequately fits river discharge, soil moisture dynamics, and groundwater tables (Winsemius et al, 2006). Finger et al (2011) showed that the performance of a distributed hydrological model can be enhanced by including spatial datasets during calibration, for example snow depth or coverage. Unfortunately, data availability severely limits the possibilities of a multi-response calibration for global hydrological models.…”
Section: Reduction Of Uncertainty In Other Hydrological Model Outputsmentioning
confidence: 99%